1993
DOI: 10.1007/bf00177192
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an enhanced substrate requirement by marine mesophilic bacterial isolates at minimal growth temperatures

Abstract: Bacterial isolates from the subtropical southeastern continental shelf were cultured in a matrix of temperature and substrate concentrations encompassing a range of temperature and substrate concentrations equal to and exceeding natural ones. At the annual minimum temperature, marine heterotrophic bacterial isolates required higher concentrations of dissolved substrates for active growth than are usually found in seawater. We show this to result from a nonlinear interaction of the combined effects of temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 44 publications
5
81
2
Order By: Relevance
“…Our results concur with those of Wiebe et al [47], who also found seasonal differences in microbial food web regulation in a mesotrophic, prealpine lake. In that study, bacterial or protozoan uptake of DOM produced from phytoplankton during winter and early spring was low, permitting greater energy flow to zooplankton and benthic animals.…”
Section: Discussionsupporting
confidence: 93%
“…Our results concur with those of Wiebe et al [47], who also found seasonal differences in microbial food web regulation in a mesotrophic, prealpine lake. In that study, bacterial or protozoan uptake of DOM produced from phytoplankton during winter and early spring was low, permitting greater energy flow to zooplankton and benthic animals.…”
Section: Discussionsupporting
confidence: 93%
“…Weak reactivity of bacteria to phytoplankton blooms in the Southern Ocean has been explained on the grounds that low temperature limits bacterial response by reducing their growth and enhancing their substrate requirements (Wiebe et al 1993;Pomeroy and Wiebe 2001). In addition, the unsuitability of the macromolecular nature of the organic matter derived from the blooms of large Antarctic diatoms to be readily used by bacteria has been proposed to explain this weak reactivity (Fiala and Delille 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, from date 4-5 (May-June, P1), and date 12-13 (August, P3), the increase in GP is related to an increase in respiration rates. Although the lack of bacterioplankton data limits the interpretation of these findings, high temperatures were recorded on day 5 and 13, which usually favours picoheterotrophic activity (Wiebe et al, 1993). Additionally, on both occasions there was a peak for ciliate abundance, the best biological predictor of DCR according to Spearman's correlation.…”
Section: Production and Respiration Ratesmentioning
confidence: 95%